2020
DOI: 10.1155/2020/2679409
|View full text |Cite
|
Sign up to set email alerts
|

β‐Sitosterol Protects against Myocardial Ischemia/Reperfusion Injury via Targeting PPARγ/NF‐κB Signalling

Abstract: Myocardial ischemia/reperfusion (I/R) injury is a clinically severe complication, which can cause high rates of disability and mortality particularly in patients with myocardial infarction, yet the molecular mechanisms underlying this process remain unclear. This study aimed to explore the protective effects of β-sitosterol against myocardial I/R injury and to elucidate the underlying molecular mechanisms. Our results showed that hypoxia/reoxygenation (H/R) treatment suppressed cell viability, induced cell apo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…Quercetin is an important flavonoid that has been normally viewed as a great antioxidant and anti-inflammatory molecule [ 35 37 ] and can prevent endothelial dysfunction and myocardial ischemia [ 38 ]. Beta-sitosterol exerted protective actions against myocardial injury [ 39 ] and is used in the treatment of hypercholesterolemia [ 40 ]. Kaempferol has antioxidant, anti-inflammatory effect [ 41 ] and protects against cardiac hypertrophy [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin is an important flavonoid that has been normally viewed as a great antioxidant and anti-inflammatory molecule [ 35 37 ] and can prevent endothelial dysfunction and myocardial ischemia [ 38 ]. Beta-sitosterol exerted protective actions against myocardial injury [ 39 ] and is used in the treatment of hypercholesterolemia [ 40 ]. Kaempferol has antioxidant, anti-inflammatory effect [ 41 ] and protects against cardiac hypertrophy [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, β -sitosterol could reduce the LPS-induced expression of PTGS2 and exert anti-inflammatory and analgesic effects [ 36 ]. Kaempferol, β -sitosterol, and sesamin can enhance insulin resistance, protect myocardial cells from injury, and prevent hyperlipidemia by increasing the expression of PPARG [ 37 , 38 ]. Sesamin also reduced the overexpression of PTGS2 by regulating the JNK and p38 MAP kinase pathways [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IRI leads to a high mortality rate in patients with MI, which is a serious clinical complication and affects the prognosis of these patients. Oxidative stress, cardiomyocyte apoptosis and cardiac dysfunction are all associated with IRI ( 18 , 19 ). It has been previously reported that intervention in cardiomyocyte apoptosis can restore IRI to a certain extent ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Oxidative stress, cardiomyocyte apoptosis and cardiac dysfunction are all associated with IRI ( 18 , 19 ). It has been previously reported that intervention in cardiomyocyte apoptosis can restore IRI to a certain extent ( 19 ). The present research also suggested that miR-24 can decrease cardiomyocyte apoptosis caused by IRI.…”
Section: Discussionmentioning
confidence: 99%